Social democracy in the periphery? The case of the RPP of Turkey - Emre, Yunus. (Thesis (Ph.D.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2011., 2011)
This dissertation is a study the entry of social democracy to the political agenda in Turkey. It examines the political context of this process. In the analysis of this process, the dissertation scrutnizes political developments within the RPP and inner party struggles for the left of center. However, it focuses on the influence of the newly emerging left movements on the Republican People‘s Party, and conceptualizes this influence as the primary reason for Republican People‘s Party‘s position change. The relations between those actors and the influence of the newly emerging left on the RPP‘s coming to the left of center position is shown via three widely debated issues of the period, land reform, anti-imperialism and anti-americanism and planned development. The research was based on primary sources, among which were official party documents and reports, documents of the actors on the left, newspaper reports, journals of the period. The conclusions reached in the dissertation are as follows: There was a difference between the historical trajectories of social democratic movements in Western Europe and in the periphery. In the periphery, the questions pertaining to economic development were more significant than class-related ones. So in this dissertation, it is claimed that the absence of European type of social democratic formations in Turkey can be traced back to the political developments around the adoption of a left of center position by the RPP in the 1960s.
Keywords: Political parties -- Turkey.; Socialism -- Turkey.; Turkey -- Politics and government -- 1960-1980.